The Development of Smart Nursing Tadpoles Farm (Hoplobatrachus rugulosus) - Iniam , Prinyawat; Intaravicha, Nuttakorn (Journal of Vocational Education in Agriculture, 2024)
The objective of this study was to design and development of smart nursing tadpoles farm (Hoplobatrachus rugulosus). The research was divided into 3 sections as follows: 1) An analysis of the environmental structure of the traditional nursing tadpoles farm of The Department of Fisheries, The college of Agriculture and Technology, Nakhon Si Thammarat by designing a set of meteorological data recorders in the IoT system and analyzing the size and direction of the relationship between environmental structures by using a correlation coefficient. 2) An experimental study of factors influencing the growth of the tadpoles was compared by comparing the growth rates and survival rates of the tadpoles from traditional and non change water nursery. 3) To design a smart nursing tadpoles farm system by considering the relationship of environmental structure, water quality data and growth rate and growth of tadpoles The results of the study revealed that the Meteorological Data Recording System IoT is accurate according to the Test Accuracy Ratio Level Standards principle. Light intensity and air temperature are related in the same direction (r=0.659). Light intensity and relative humidity are related in opposite directions (r=-0.627). Light and water temperature were related in the same direction (r=0.543), weight, length and survival rate of tadpoles from the traditional nursing more than the non-water change nursing were statistically significant (P<0.05). The smart nursing tadpoles farm was equipped with a camouflage net to control the light intensity to be in the range of 900 –2,100 Lux turbidity measurement device light intensity, relative humidity and air temperature. When the processing system receives the relative humidity and/or air temperature data above the appropriate level. The system will spray water to control the relative humidity and when the turbidity data is obtained by the processor above the appropriate level The system will automatically change the water.